2013
DOI: 10.1002/cbin.10158
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide SP activates the WNT signal transduction pathway and enhances the proliferation of bone marrow stromal stem cells

Abstract: Substance P (SP) mediates multiple activities in various cell types, such as proliferation, anti-apoptotic response, and inflammation. We have investigated the effects of SP, NK1 antagonist and DKK1 on proliferation of bone marrow stromal stem cells (BMSCs), as well as the underlying mechanism. Isolated BMSCs were exposed to SP (10(-8)  M) (group A), SP + NK1 antagonist (1 µM) (group B), SP + DKK1 (0.2 µg/mL) (group C), or the same amount of PBS (group D). Expression of gene and protein of Wnt/β-catenin signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…SP is known to phosphorylate protein kinase Akt, which has antiapoptotic effects [18]. SP is also found to be involved in the proliferation of bone marrow stem cells via WNT signaling pathway [19] but it has to be studied in detail in the proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…SP is known to phosphorylate protein kinase Akt, which has antiapoptotic effects [18]. SP is also found to be involved in the proliferation of bone marrow stem cells via WNT signaling pathway [19] but it has to be studied in detail in the proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human bone marrow mononuclear cells and fibroblasts also proliferate in response to substance P (Rameshwar et al, 2001b). Furthermore, it has been shown that SP could enhance proliferation of bone marrow stem cells (Mei et al, 2013). …”
Section: Immunobiology Of Substance Pmentioning
confidence: 99%
“…To identify the first changes in the expression of BMP-2 and VEGF, observations were made on 1 day, 3 days, 5 days, and 7 days; these intervals were also employed to determine the effects of SP on the migration of the BMSCs. The concentration of SP (10 −8  mol/L) was chosen for the possible maximum effect [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the expression of osteoblastic genes and proteins is vital to bone generation [16], and Wnt signaling is an important regulatory factor in bone metabolism [1719]. SP has been confirmed to exert a promoting effect on the proliferation and differentiation of BMSCs [2024]. However, the effect of SP on BMP-2 expression is currently unclear.…”
Section: Introductionmentioning
confidence: 99%